PET Quantification in Healthy Humans of Cyclooxygenase-2, a Potential Biomarker of Neuroinflammation - Yan, Xuefeng; Noergaard, Martin; Morse, Cheryl L; Liow, Jeih-San; Hong, Jinsoo; Greve, Douglas; Telu, Sanjay; Kim, Min-Jeong; Montero Santamaria, Jose A; Galassi, Anthony; Feng, Ningping; Williams Avram, Sarah K; et al. (The Journal of nuclear medicine (1978), 2025)
Cyclooxygenase-2 (COX-2) is present in a healthy brain at low densities but can be markedly upregulated by excitatory input and by inflammogens. This study evaluated the sensitivity of the PET radioligand [ C]-6-methoxy-2-(4-(methylsulfonyl)phenyl)- -(thiophen-2-ylmethyl)pyrimidin-4-amine ([ C]MC1) to detect COX-2 density in a healthy human brain. The specificity of [ C]MC1 was confirmed using lipopolysaccharide-injected rats and transgenic mice expressing the human gene, with 120-min baseline and blocked scans using COX-1 and COX-2 selective agents. Twenty-seven healthy participants were injected with [ C]MC1. Ten of these participants received 2 PET scans: a baseline study followed by blockade with celecoxib (600 mg orally), a preferential COX-2 inhibitor. Seventeen participants underwent test-retest imaging. All scans included concurrent arterial sampling. The tissue-to-plasma ratio at equilibrium (i.e., total distribution volume) was determined using a 2-tissue compartment model (2TCM). In humanized transgenic COX-2 mice, 70%-90% of [ C]MC1 brain uptake was blocked by nonradioactive MC1 and celecoxib (a COX-2 selective inhibitor) but not by PS13 (a COX-1 selective inhibitor), thereby confirming specific binding to human COX-2. Radioactivity in the human brain peaked at a concentration of about 4.0 SUV, indicating good passage through the blood-brain barrier. Values for the total distribution volume achieved stability after 80 min, indicating no radiometabolite contamination. Celecoxib reduced radioligand binding in neocortical areas by 25% but had little or no effect in subcortical regions and the cerebellum, which correlated with COX-2 messenger RNA expression levels. Binding site occupancy by celecoxib was virtually complete, as determined by the Lassen plots. Test-retest reliability was moderate (intraclass correlation coefficient, 0.65) but had relatively large variability (absolute retest variability, 20%). Reference tissue methods yielded results comparable to those of 2TCM but reduced retest variability by up to 75% and reduced intersubject variability (coefficient of variation) by about half. Thus, compared with 2TCM, which requires arterial blood, the reference tissue method is expected to significantly reduce the sample sizes required to detect statistically significant differences between groups. [ C]MC1 has adequate sensitivity to measure the low density of COX-2 in a healthy human brain, suggesting it can also quantify the COX-2 elevations expected in human disorders associated with neuroinflammation.